2021
DOI: 10.1097/rli.0000000000000766
|View full text |Cite
|
Sign up to set email alerts
|

The Rate of Apparent Diffusion Coefficient Change With Diffusion Time on Breast Diffusion-Weighted Imaging Depends on Breast Tumor Types and Molecular Prognostic Biomarker Expression

Abstract: Introduction:The aim of this study was to investigate the variation of apparent diffusion coefficient (ADC) values with diffusion time according to breast tumor type and prognostic biomarkers expression. Materials and Methods: A total of 201 patients with known or suspected breast tumors were prospectively enrolled in this study, and 132 breast tumors (86 malignant and 46 benign) were analyzed. Diffusion-weighted imaging scans with 2 diffusion times were acquired on a clinical 3-T magnetic resonance imaging sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 39 publications
3
15
0
Order By: Relevance
“…The observed decrease in ADC and sADC values with T d in breast tumors was in agreement with the literature, as were the results of our previous investigation 11,32,42 . This con rms the hypothesis that diffusion hindrance in tumors increases when the T d value increases, as more molecules might hit the increased number of obstacles such as cell membranes.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The observed decrease in ADC and sADC values with T d in breast tumors was in agreement with the literature, as were the results of our previous investigation 11,32,42 . This con rms the hypothesis that diffusion hindrance in tumors increases when the T d value increases, as more molecules might hit the increased number of obstacles such as cell membranes.…”
Section: Discussionsupporting
confidence: 92%
“…A previous study that compared between benign and malignant tumors revealed greater ADC change in malignant than benign lesions 32,42 . In this study, we assumed that more malignant pathological features like active proliferation, tight structure, and small cell spacing hinder the diffusion of water molecules inside tissue and ultimately decrease the ADC value in MDA-MB-231 tumors.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…We found that the ΔADC 2.5 _sADC 27.6 using different T d values had a significant positive correlation with APT SI. Previous studies have reported that time-dependent DWI or CEST imaging might provide information about tumor microstructure indicating tumor proliferation in oncologic imaging 29 33 . Comparisons of APT SI and IVIM parameters in cervical cancers 34 , gliomas 35 , and hepatocellular carcinomas 36 , as well as comparisons of APT SI and diffusion kurtosis imaging in rectal carcinomas 37 , have been reported.…”
Section: Discussionmentioning
confidence: 99%